"Strong beats skinny every time": Disordered eating and compulsive exercise in women who post fitspiration on Instagram. Issue 1 (15th June 2016) - Holland, Grace; Tiggemann, Marika
ABSTRACT: Objective: Fitspiration is a recent Internet trend designed to motivate people to eat healthily and to exercise. The aim of the study was to investigate disordered eating and exercise in women who post fitspiration on Instagram. Method: Participants were 101 women who post fitspiration images on Instagram and a comparison group of 102 women who post travel images. Both groups completed measures of disordered eating and compulsive exercise. Results: Women who post fitspiration images scored significantly higher on drive for thinness, bulimia, drive for muscularity, and compulsive exercise. Almost a fifth (17.5%) of these women were at risk for diagnosis of a clinical eating disorder, compared to 4.3% of the travel group. Compulsive exercise was related to disordered eating in both groups, but the relationship was significantly stronger for women who post fitspiration images. Discussion: For some women, posting fitspiration images on Instagram may signify maladaptive eating and exercise behaviors. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2017; 50:76–79)